Looking at children - Behrens, June. (Chicago : Childrens Press, 1977)
Discusses the subjects and artistic techniques of fourteen sculptures and paintings from the fifth century B.C. to the present day.
"A Golden Gate junior book."
Keywords: Children in art -- Juvenile literature; Art appreciation -- Juvenile literature; Children in art; Art appreciation